Pleural cryptococcosis diagnosed by pleural biopsy in an immunocompromised patient: a case report - Jia, Hongxia; Liu, Hongping; Tu, Meng; Wang, Yan; He, Xudong; Zhang, Guojun (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The aim of this study is to report an isolated pleural cryptococcosis with pleural effusion as the only manifestation, confirmed by pleural biopsy in a patient with thymoma combined with myasthenia gravis, who developed pleural effusion of unknown origin after long-term glucocorticoids and tacrolimus therapy. Methods Pathological examination of the right pleural biopsy tissue from a patient with unexplained recurrent pleural effusion was implemented. Morphological analysis of the fungal component and metagenomic next-generation sequencing (mNGS) on the pleural tissue were performed. Results A biopsy specimen of the right pleura revealed numerous yeast-like organisms surrounded by mucous capsules and Cryptococcus neoformans was detected by mNGS with a species-specific read number (SSRN) of 4, confirming the diagnosis of pleural cryptococcosis. Pleural effusion was eliminated with amphotericin B and fluconazole, and healthy status was maintained at the time of review 1 year later. Conclusion Cryptococcosis, manifested by simple pleural effusion, is extremely rare, but when repeated pleural effusion occurs in immunocompromised patients or in patients with malignant tumors, the possibility of cryptococcosis should be treated with high vigilance and pleural biopsy is recommended if necessary in order to confirm the diagnosis.